Profession differences in revealed risk preferences: An empirical analysis of Doctors, Accountants and Insurance Employees - Irodotou, Pavlina (2016)
The main objective of this study is to examine the occupational differences in the revealed risk preferences of doctors, accountants and insurance employees. Past researchers have consistently studied the individual differences in risk preferences considering several factors such as age, gender and education, but did not explore the variations in risk preferences between people in different occupations. Therefore, this study attempts to fill this gap in the literature by investigating the impact of a group of professions on risk preferences. An experimental study has been conducted using 266 questionnaires from doctors, accountants and insurance employees, both in the UK and Cyprus, and aimed to explore the way that individuals in different professions perceive their risk preferences to be and the way they react under hypothetical gambling and real-life activities. This research finds evidence that accountants are more risk averse than insurance agents and doctors, and that gender within an occupation does not have a significant impact on the risk preferences of individuals. Finally, this study finds evidence that participants’ perceived, hypothetical and real-life risk preferences are not associated which explains the fact that people react in different ways when they are exposed to different sources of risk. The diversification of risk preferences among occupations entails significant implications since it appears that their occupational background affects the way in which individuals deal with general and job related risks.